(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Research shows that organizations need employee energies to function, resulting in the processes of creation, the achievement of goals, and collaboration at all levels. In this research study, we are interested whether there exists an interrelated influence of Organizational Energy (Productive Energy, Comfortable Energy, Resigned Inertia, Corrosive Energy) and Autopoietic Endowments (Self-Awareness, Conscience, Independent Will, Creative Imagination) of employees. We selected Works Council members in Slovenian organizations as the target group for conducting the research study. Purpose: The purpose of the research was to examine the interrelated influence of organizational energy and autopoietic endowments of employees, assuming that a higher level of autopoietic endowments is reflected in a higher value of quality organizational energy. The purpose of this study was also to verify the research instrument. Method: We used a questionnaire as a measuring instrument to collect information for the pilot research. The questionnaires were based on two existing questionnaires and scholarly literature in our field of interest. Results: The research findings confirm the interrelatedness between Autopoietic Endowments and Organizational Energy of Works Council members. However, to check the influence of the independent variable on the dependent one, a larger sample would be needed. The results also revealed that the participants in the study had a higher value of quality- than low-quality energies, which indicates the participants constructive use of personal potentials. Organization: The existence of interrelated influences of Autopoietic Endowments and Organizational Energy is an important insight for organizations that contributes to the understanding of organizational energy management. Society: The conducted research represents a contribution to new findings in the field of implementation of workers’ participation in organizations in Slovenia. Originality: There is a dearth amount of research on the topics and the authors did not find research that intertwines organizational energy and the principles of autopoiesis in the context of workers’ participation, either in Slovenia or globally. Limitations / further research: The research was conducted in the form of a pilot study to verify the reliability of the questionnaire. The pilot study could be extended to a larger sample, but due to the separation of participants between the pilot and the main research, we decided to obtain a larger sample in the primary research. However, we tried to overcome the limitation by looking for a sample greater than 25, which is an acceptable number for conducting a pilot study to test the questionnaire.